Oxford Handbooks Online 2018
DOI: 10.1093/oxfordhb/9780190464745.013.14
|View full text |Cite
|
Sign up to set email alerts
|

Mind-Wandering and Self-Referential Thought

Abstract: When our mind wanders, we frequently experience thoughts, images, and feelings about ourselves and our life. These self-referential thoughts involve diverse contents and take various forms, but most often focus on specific future events that are closely related to our personal goals and concerns. Neuroimaging studies show that such spontaneous mentations recruit many of the same brain regions-largely corresponding to the default network-as directed self-referential thought. The medial prefrontal cortex is most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 107 publications
1
17
0
Order By: Relevance
“…Interestingly, psychedelic drugs have been shown to decrease activity in the mPFC and PCC as well (Carhart-Harris et al, 2012 ; Palhano-Fontes et al, 2015 ). These nodes of the DMN have been shown to be more active during various types of self-related stimuli (Northoff et al, 2006 ; Sugiura et al, 2008 ; Qin and Northoff, 2011 ; Tacikowski et al, 2017 ), self-reflection (Jenkins and Mitchell, 2011 ; D'Argembeau, 2018 ) and autobiographical memory retrieval (Cabeza and St Jacques, 2007 ). A recent study using dynamic causal modeling suggested that self-referential processes are driven by PCC activity and modulated by the regulatory influences of the mPFC (Davey et al, 2016 ).…”
Section: Alterations Of Self-consciousness Induced By Meditation and mentioning
confidence: 99%
“…Interestingly, psychedelic drugs have been shown to decrease activity in the mPFC and PCC as well (Carhart-Harris et al, 2012 ; Palhano-Fontes et al, 2015 ). These nodes of the DMN have been shown to be more active during various types of self-related stimuli (Northoff et al, 2006 ; Sugiura et al, 2008 ; Qin and Northoff, 2011 ; Tacikowski et al, 2017 ), self-reflection (Jenkins and Mitchell, 2011 ; D'Argembeau, 2018 ) and autobiographical memory retrieval (Cabeza and St Jacques, 2007 ). A recent study using dynamic causal modeling suggested that self-referential processes are driven by PCC activity and modulated by the regulatory influences of the mPFC (Davey et al, 2016 ).…”
Section: Alterations Of Self-consciousness Induced By Meditation and mentioning
confidence: 99%
“…Self-as-object thus greatly resembles Duval and Wicklund’s (1972) concept of “objective self-awareness,” when attention is directed inward and one’s attention is focused on oneself in which case one becomes the target of ones’ own attention. Brain regions typically activated during self-as-object experiences include the medial prefrontal cortex, posterior cingulate/precuneus, inferior parietal lobules, and areas of the medial and lateral temporal lobes (D’Argembeau, 2018). These brain areas are also recruited during rest (i.e., default mode network) typically implicated in self-directed cognition (Buckner et al, 2008).…”
Section: Two Types For Self-experiencesmentioning
confidence: 99%
“…Second, from a phenomenological perspective, dreams are at core immersive, involving a simulated world centered on a simulated self (Windt, 2015; Windt et al, 2016). Similarly, daydreams tend to be focused on self-related concerns (D’Argembeau, 2018) and often contain vivid audio-visual imagery as well as emotions (Foulkes and Fleisher, 1975). Yet, daydreams lack the “here and now” quality of sleep dreams: in wakefulness, we don’t lose touch with our actual environments or feel present in imagined ones as completely as we do in sleep-dreams.…”
Section: Introductionmentioning
confidence: 99%